Analisis Content Marketing Pada Tiktok Berdasarkan Persepsi Buyer - Vidyastuti, Heppy Agustiana (Journal of Innovation in Management, Accounting and Business, 2024)
This study aims to gather insights on buyer perceptions of content marketing on TikTok in order to improve content marketing strategies. The research method employed was quantitative research with a descriptive approach, involving 200 buyer respondents in the city of Bandung. The study focuses on TikTok marketing, with dimensions derived from various reviewed journals. A questionnaire was used as the research instrument, distributed to buyers through accidental sampling. Descriptive statistical analysis was conducted to analyze the data. The research findings indicate that TikTok marketing on content marketing is well-received, with the lowest value observed in the accuracy dimension and the highest value in the easy-to-find aspect. The three dimensions with the highest average value are ease of finding content marketing, collaboration with influencers, and the level of interest in TikTok content marketing. This research provides valuable input for the improvement of content marketing strategies on TikTok, benefiting TikTok shops and contributing to the development of content marketing in the field of digital marketing.